Public Law and Economics - Robert Cooter; Michael Gilbert (Oxford University Press, 2022)
This comprehensive textbook applies economic analysis to public law. The economic analysis of law has revolutionized legal scholarship and teaching in the last half-century, but it has focused mostly on private law, business law, and criminal law. This book extends the analysis to fundamental topics in public law, such as the separation of government powers, regulation by agencies, constitutional rights, and elections. Every public law involves six fundamental processes of government: bargaining, voting, entrenching, delegating, adjudicating, and enforcing. The book devotes two chapters to each process, beginning with the economic theory and then applying the theory to a wide range of puzzles and problems in law. Each chapter concentrates on cases and legal doctrine, showing the relevance of economics to the work of lawyers and judges. Featuring lucid, accessible writing and engaging examples, the book addresses enduring topics in public law as well as modern controversies, including gerrymandering, voter identification laws, and qualified immunity for police.
Keywords: 340; law and economics; interpretive economics; constitutional economics; economics of rights; economics of bargaining; economics of voting; economics of entrenchment; economics of delegation; economics of adjudication; economics of enforcement